2021
DOI: 10.18844/wjet.v13i3.5948
|View full text |Cite
|
Sign up to set email alerts
|

Fostering post-secondary vocational students’ critical thinking through multi-level tasks in learning environments

Abstract: In today’s labour market, being competitive requires, in addition to technical skills, several twenty-first-century career competencies, including the capacity to think critically. Although the literature on teaching methods designed for enhancing students’ reflective thinking abounds, the contribution of special tasks with varying complexity to learners’ critical thinking capacity, to our knowledge, has not been earlier investigated. Hence, the present investigation sought to investigate the effect of multi-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In our study, the teachers of these schools in their pedagogical practice use to a greater extent these traditional tests to assess the knowledge of students. The research of Bekbayeva et al, (2021), was suggested to have application for educational initiatives targeted at improving students' academic performance by promoting their critical thinking (Bekbayeva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the teachers of these schools in their pedagogical practice use to a greater extent these traditional tests to assess the knowledge of students. The research of Bekbayeva et al, (2021), was suggested to have application for educational initiatives targeted at improving students' academic performance by promoting their critical thinking (Bekbayeva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%